PROSA MATCH Model Student Learning Solutions : Evidance Elementary School - Ranah (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
This research uses Classroom Action Research (CAR), which was conducted in four meetings. The research subjects were fourth grade students of SDN 9 Kampung Baru Simpang Empat, Tanah Bumbu Regency for the academic year 2020/2021, the number of students was 18. The types of data in this study were qualitative and quantitative data, through observation of teacher and student activities and quantitative data obtained through measurement techniques. with an individual written test. The data analysis used was qualitative and quantitative. The results of this study indicate that the teacher's activity in meetings 1 to 4 increased from 28 to 37. Student activity at meetings 1 to 4 increased from 66.67% to 94.45%. Students' critical thinking skills at meetings 1 to 4 increased from 66.67% to 94.45%. Learning outcomes of cognitive aspects from 66.67% to 100%. Affective learning outcomes at meetings 1 to 4 increased from 61.11% to 94.45%. Psychomotor learning outcomes at meetings 1 to 4 increased from 55.56% to 94.45% classically. Based on these findings, it can be concluded that the PROSA MATCH Model, namely the Combination of Problem Based Learning (PBL), Jigsaw, and Make A Match Models can improve teacher activities, activities and critical thinking skills as well as student learning outcomes. It is recommended to use this model as an alternative in increasing student activity which has an impact on improving student learning outcomes..